2014
DOI: 10.1002/ange.201311114
|View full text |Cite
|
Sign up to set email alerts
|

The Bioinorganic Chemistry of Apoptosis: Potential Inhibitory Zinc Binding Sites in Caspase‐3

Abstract: Zn 2+ inhibits the action of several of the caspases and thus may act as a regulator of apoptosis. Reversal of this inhibition is one possible approach for the development of apoptosis-based therapies. Few studies describe the molecular details of the Zn 2+ -caspase interaction, the understanding of which is essential for the success of any therapeutic strategies. Enzyme kinetics and biophysical studies have shown that the inhibition is of mixed type with prominent (ca. 60 % of inhibition) uncompetitive charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
2
20
0
1
Order By: Relevance
“…Similar zinc coordination sites are observed in the crystal structures of caspase-3 and mammalian NOS regulator dimethylarginine dimethylaminohydrolase. In caspase-3, the residues Cys163 and His121 along with two water molecules stabilize the Zn ion in the active site 36 . In the structure of the mammalian NOS regulator dimethylarginine dimethylaminohydrolase, the Cys273 and His172 along with two water molecules stabilize the Zn ion in the active site with Asp78 residue showing coordination with water molecules 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar zinc coordination sites are observed in the crystal structures of caspase-3 and mammalian NOS regulator dimethylarginine dimethylaminohydrolase. In caspase-3, the residues Cys163 and His121 along with two water molecules stabilize the Zn ion in the active site 36 . In the structure of the mammalian NOS regulator dimethylarginine dimethylaminohydrolase, the Cys273 and His172 along with two water molecules stabilize the Zn ion in the active site with Asp78 residue showing coordination with water molecules 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Caspase‐3 has a role in the apoptotic cascade, and it is mostly used to measure cell apoptosis . In this study, we evaluated the tissue caspase‐3 activity in the study groups, and we observed the highest levels in the torsion/detorsion + saline group (group 3).…”
Section: Discussionmentioning
confidence: 86%
“…Caspase-3 has a role in the apoptotic cascade, and it is mostly used to measure cell apoptosis. 42 In this study, we evaluated the tissue caspase-3 activity in the study groups, and we observed the highest levels in the torsion/detorsion + saline group (group 3). High-dose metformin administration after IRI enhanced the tissue caspase-3 activity, but we could not demonstrate the same effect for low-dose metformin administration.…”
Section: Discussionmentioning
confidence: 90%
“…As reported by others (Chimienti et al, 2001;Corniola et al, 2008;Bozym et al, 2010;Pang et al, 2012Pang et al, , 2013Strand et al, 2013), cleaved capase-3 (active caspase) was increased significantly in TPEN-treated cNCC. Zn is an endogenous inhibitor of CC3; removal of Zn from procaspase inhibitory binding sites results in the auto-proteolytic cleavage transformation of the zymogen into an active effector capase3 (Peterson et al, 2009;Daniel et al, 2014). This inhibition requires the maintenance of relatively high intracellular (nM) Zn ion concentrations (Maret et al, 1999;Maret, 2011).…”
Section: Discussionmentioning
confidence: 99%